1990
DOI: 10.1128/aac.34.5.863
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic inhibition of the respiratory burst response in human polymorphonuclear leukocytes

Abstract: Recently we found that certain antibiotics which are markedly concentrated by human polymorphonuclear leukocytes (PMN) failed to kill susceptible, intraphagocytic Staphylococcus aureus, even though cellular drug levels were quite high. The possibility that specific antibiotics might adversely affect phagocyte antibacterial function was considered. Thus, we studied the effects of multiple antibiotics and adenosine, a known modulator of the PMN respiratory burst response, on neutrophil antibacterial function. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 38 publications
1
51
0
Order By: Relevance
“…In addition, it is hypothesized that this high concentration of EM within the neutrophil cytoplasm may modulate neutrophil functions. In fact, EM-mediated inhibition of neutrophil chemotaxis (9,27,29,31,32), oxidant generation (1,13,27), and phagocytosis (27) have been reported. In addition, EM also shortens neutrophil survival by accelerating apoptosis (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is hypothesized that this high concentration of EM within the neutrophil cytoplasm may modulate neutrophil functions. In fact, EM-mediated inhibition of neutrophil chemotaxis (9,27,29,31,32), oxidant generation (1,13,27), and phagocytosis (27) have been reported. In addition, EM also shortens neutrophil survival by accelerating apoptosis (2).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 4 shows the effects of pretreatment with macrolide antibiotics (EM, CAM, RXM, and AZM) on macrophage cytocidal activity against Candida albi- Antibiotics have biological properties other than direct antimicrobial activity. These include interactions with and alteration in the functions of host phagocytic cells (4,13,15,28). This subject is of importance, since phagocytic cells are essential for controlling almost all infections and are mediators of inflammation.…”
Section: Methodsmentioning
confidence: 99%
“…However, only recently have investigators begun to elucidate the mechanisms by which such antibiotics counteract inflammation. These mechanisms may include the reduction of PMN and mononuclear leukocyte infiltration [25,31], the inhibition of pro-inflammatory cytokine expression in PMN, monocytes, and epithelial cells [24,27,32,44], the inhibition of PMN adhesion to epithelial cells [24,26], and the suppression of the PMN oxidative burst [15,32,45]. In addition, recent studies have demonstrated the ability of several macrolides and azalides, including erythromycin and azithromycin, to induce PMN apoptosis in vitro [7,16,20,28].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that antibiotics with antibacterial and antiinflammatory action are good options in containing both the infectious agent as well as the harmful action of the overstimulated immune response. The macrolide group of antibiotics have been known to affect several pathways of inflammatory processes such as migration of neutrophils, oxidative burst in macrophages, and the production of pro-inflammatory cytokine [5,6], but because of the various side effects of antibiotics and the problem of ever-increasing antibiotic resistance, there has been a shift towards alternative or complementary ways of medicine. One such approach being explored is the use of herbal compounds.…”
Section: Introductionmentioning
confidence: 99%